Transoral Robotic Surgery for Early-T Stage Glottic Cancer Involving the Anterior Commissure—News and Update - Wang, Chen-Chi; Lin, Wen-Jiun; Wang, Jing-Jie; Chen, Chien-Chih; Liang, Kai-Li; Huang, Yen-Jung (Frontiers in Oncology, 2022)
Background About 20% of all glottic carcinomas involve the anterior commissure (AC), and AC involvement was deemed to be a risk factor of local recurrence and poor prognosis. Transoral robotic surgery (TORS) has been developed for a panoramic view of the AC and en-bloc resection of the tumor by multidirectional dissection with endo-wristed instruments. With satisfactory preliminary results, we would like to update the data with a bigger cohort and present the news on using TORS for salvage treatment of recurrence from irradiation failure. Methods From July 2010 to December 2019, 22 patients with early T1 and 2 stage primary (n = 11) or recurrent (n = 11) glottic cancer with AC involvement received TORS without adjuvant therapy. TORS exposure was found to be better than TLM by conventional laryngoscopy in diagnostic biopsy. Seven of the 22 patients had recurrent cancer from irradiation failure. The perioperative factors that may be associated with survival were retrospectively analyzed, and the 5-year overall survival (OS)/disease-specific survival (DSS)/recurrence-free survival (RFS)/and organ preservation survival (OPS) rate were estimated by the Kaplan–Meier Method. Their voice and swallowing functions were evaluated by questionnaires of Voice Handicap Index-10 (VHI-10) and Functional Outcome Swallowing Scale (FOSS). Results All 22 TORSs were completed smoothly. After a mean follow-up of 49 ± 35.9 months, the Kaplan–Meier method estimated 5-year OS/DSS/RFS/OPS was 93.8%, 93.8%, 74.6%, and 86.3%, respectively. Our 11 patients with fresh cancer had 100% recurrence-free survival. Although the recurrent rate was higher in patients with history of RT, they could be rescued by further open laryngectomy without compromising the OS and DSS. Only one patient expired. The other 21 patients had satisfactory swallowing function with FOSS of 0.33 ± 0.66. Five patients depended on tracheostomy, but the rest 17 patients had serviceable voice with VHI-10 of 18.41 ± 11.29. Conclusions TORS could be used in the primary or salvage management of glottic cancer with AC involvement while TORS was confirmed to have better exposure to TLM. The RFS was good for patients with primary cancer. In patients having irradiation failure, TORS could also be a minimally invasive transoral approach before trying open surgery to preserve the organ.